Analyzing Undergraduate Students’ Errors in Writing Descriptive Text - Aisyah, Noor; Yulianto, Puguh Setiyawan (Journal of Language Intelligence and Culture, 2022)
This study aimed to identify the students’ errors and find the most errors students made. This study used qualitative approach having descriptive approach the research method. The sample were 35 college students in the University at the first semester in English class which selected purposively. The data was collected through the writing test. It is used to identify the type of errors students’ made and the highest errors students’ made in writing descriptive text by using simple present tense. The writing test is conducted two times. After those, the data were analyzed and found the result. The result showed that there were 510 errors found in students’ works, consisting of omission of “be”, inappropriate use of “be”, superfluous of be, subject-verb agreement, wrong form of have/has, wrong form of negative sentence, inappropriate use of pronoun and wrong form of modal auxiliary. The highest number of errors was subject-verb agreement at the first rank with 138 errors or 27% and omission “be” after subject at the second rank with 125 errors or 22.5% and the lowest numbers of error were inappropriate use of pronoun and inappropriate form of negative sentence with 11 error or 2.2 %.  Based on the result, it can be found that students have difficulties in writing descriptive text by using simple present tense which influenced of interlanguage transfer and intralingual transfer.